Access control oriented quantified trust degree representation model for distributed systems - LANG Bo (Tongxin xuebao)
Based on the research fruit of social trust in sociology,the semantics,properties and elements of trust in the context of access control of distributed systems were defined.By combining fuzzy set theory with probability theory,a mathematical definition of trust was given,a quantified trust degree representation model including an integrated trust evaluation model and a trust calculating algorithm was established.The model integrates multiple elements of trust,and is in accordance with the decreasing and enhancing rules of the recommended trust.